Variation in summer nitrogen and phosphorus uptake among Siberian headwater streams - John D. Schade; Erin C. Seybold; Travis Drake; Seth Spawn; William V. Sobczak; Karen E. Frey; Robert M. Holmes; Nikita Zimov (Polar Research, 2016)
Arctic streams are likely to receive increased inputs of dissolved nutrients and organic matter from thawing permafrost as climate warms. Documenting how Arctic streams process inorganic nutrients is necessary to understand mechanisms that regulate watershed fluxes of permafrost-derived materials to downstream ecosystems. We report on summer nitrogen (N) and phosphorus (P) uptake in streams draining upland soils from the Pleistocene, and lowland floodplain soils from the Holocene, in Siberia's Kolyma River watershed. Uptake of N and P differed between upland and floodplain streams, suggesting topographic variation in nutrient limitation. In floodplain streams, P uptake rate and uptake velocity were higher than N, while upland streams had similar values for all N and P uptake metrics. Phosphorus uptake velocity and size of the transient hydrologic storage zone were negatively related across all study streams, indicating strong influence of hydrologic processes on nutrient fluxes. Physical sorption of P was higher in floodplain stream sediments relative to upland stream sediments, suggesting more physically driven uptake in floodplain streams and higher biological activity in upland streams. Overall, these results demonstrate that high-latitude headwater streams actively retain N and P during summer base flows; however, floodplain and upland streams varied substantially in N and P uptake and may respond differently to inorganic nutrient and organic matter inputs. Our results highlight the need for a comprehensive assessment of N and P uptake and retention in Arctic streams in order to fully understand the impact of permafrost-derived materials on ecosystem processes, and their fate in continental drainage networks.